ENT 530 Social Media Portfolio: DK's Bakery / DK Siti Nursyuhada PG Zaidi - PG Zaidi, DK Siti Nursyuhada (2021)
Dk's Bakery is the name of our business. The main products of Dk's Bakery are Florentine Cookies, which come in two flavours: Original Florentine Cookies and Chocolate Florentine Cookies. The major goal of the company is to provide excellent Florentine Cookies to our consumers at a reasonable price with a luxury taste and crunchy nuts.